'Literary Evenings' at the Greek National Theatre, 1945–6: popular education and the literary canon. (October 2019) - Antonelaki, Fiona
Abstract : This article recounts the little-known story of the 'Literary Evenings' (1945–6), a series of literary recitals staged at the Greek National Theatre and organized by members of the Generation of the 1930s. Set against the background of intense political rivalry that followed the Varkiza Agreement, the 'Literary Evenings' capture the post-war aspirations for the popularization of high culture. Drawing upon hitherto unexplored archival material, this article aims to offer a new, historically informed understanding of the Generation of the 1930s, while also directing attention to the aural consumption of literary texts as an unacknowledged force behind canon formation.